Australia : Mutual Evaluation Report; FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report, 2006)
The evaluation of the anti-money laundering (AML) and combating the financing of terrorism (CFT) regime of Australia was based on the Forty Recommendations 2003 and the Eight Special Recommendations on Terrorist Financing 2001 of the Financial Action Task Force (FATF), and was prepared using the AML/CFT Methodology 2004. It describes and analyses those measures and provides recommendations on how certain aspects of the system could be strengthened. It also sets out Australia's levels of compliance with the FATF 40+8 Recommendations.